Tax Increment Financing framework for integrated transit and urban renewal projects in car dependent cities - McIntosh, James; Trubka, Roman; Newman, Peter (Routledge, 2014)
Tax Increment Financing (TIF) has long been seen in the USA as a tool for urban regeneration but the use of TIF for funding transit projects is less common. A four-step Transit Tax Increment Financing (TTIF) framework is proposed as a means of funding the investment inintegrated land use and transit projects in low-density car-dependent cities. The TTIF framework is illustrated through a case study of a retrospective application to the Mandurah rail line in Perth, Western Australia, and demonstrates that much more funding can be generated using this mechanism than has been considered by transit project planners before. It also has the benefits of enabling private sector involvement in transit projects and ensures Transit Oriented Developments (TODs) are built and not just planned.